A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat reactor
Through the synthesis method of chromium ion doped tungsten oxide, the existing photohydrolysis catalyst has been solved, the problems of low efficiency, scarce raw materials and poor photocorrosion are achieved, and high-efficiency, long-life and low-cost photohydrolysis catalysts have been achieved, which has improved solar energy to Hydrogen conversion efficiency.
Patent Information
- Application Number
- CN202311633216.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-12-01
AI Technical Summary
The existing complete photohydrolysis catalyst has low efficiency, the conversion efficiency from solar energy to hydrogen is less than 1%, and the raw materials used for high-active photocatalysts are scarce and expensive, with poor light resistance and corrosion, short service life, cumbersome and complex synthesis methods, which are not conducive to scale preparation.
The synthesis method of a plate reactor of chromium ion-doped tungsten oxide complete photolysis catalyst is used. Sodium tungstate and chromium acetate are dissolved in water and mixed with glacial acetic acid, followed by heating and reaction in an autoclave, and finally annealing in vacuum. Improve the structure and activity of the catalyst.
The activity of the complete photohydrolysis catalyst is significantly improved, and the conversion efficiency of solar energy to hydrogen reaches 4.3%~6.1%, extending the service life of the catalyst and reducing its cost.
Smart Images

Figure CN117861678B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts for photolysis of water, and in particular to a method for synthesizing a chromium ion-doped tungsten oxide complete photocatalyst flat-plate reactor. Background Art
[0002] With the deepening of the concept of sustainable development, an energy structure dominated by renewable clean energy will be formed in the near future, in which hydrogen energy occupies a pivotal position and share. However, the current rate of reducing fossil fuel consumption cannot keep up with actual demand, and the production rate of clean energy is far from meeting the requirements of energy planning goals. The water reserves on the earth are huge, the sources are wide, clean and recyclable. The efficient and low-cost complete photolysis of water to produce hydrogen is regarded as one of the most effective renewable energy production and hydrogen supply strategies in the future as a sustainable, convenient, cheap and green way to generate hydrogen. Therefore, it has attracted much attention in the production of hydrogen energy and hydrogen raw materials.
[0003] The efficiency and feasibility of commercial complete photocatalytic water splitting to produce hydrogen depends on the activity of the photocatalyst, the cost of materials, and the photochemical and chemical stability, especially the appropriate electronic structure required for complete water splitting (i.e. the bottom of the conduction band is more negative than the hydrogen evolution potential and the top of the valence band is more positive than the oxygen evolution potential) and the narrowest possible band gap ensures a wider solar spectrum absorption range. Therefore, the development of a synthesis method for a complete photocatalytic water splitting catalyst with high activity, stable structure, simple synthesis process, low cost, and scalable preparation is crucial to achieve efficient photocatalytic water splitting to produce green hydrogen.
[0004] At present, the cost of producing hydrogen from water by photolysis by adding sacrificial reagents, electron mediators, and external bias is much higher than that of producing hydrogen from fossil fuels due to the use of external reagents or auxiliary equipment. It is not sustainable and cannot be applied and promoted in practice. Although there are many experimental methods for synthesizing new complete photocatalysts for water splitting, the apparent quantum yield (AQE) of hydrogen evolution is extremely low (<1%); or the raw materials used are scarce and costly (for example: compounds of rare metal elements such as gallium and indium, and expensive precious metals such as rhodium and platinum must be used as co-catalysts), and the synthesis method is cumbersome and complicated. The obtained catalysts are severely photocorroded, have poor structural stability, and have a short service life, which cannot meet the requirements of large-scale practical applications. The existing research on complete photocatalysts for water splitting is still far from the practical application of water splitting for hydrogen production and the large-scale synthesis of catalysts. Therefore, water splitting for hydrogen production cannot replace the currently widely used fossil fuel hydrogen production. Furthermore, the conduction band bottom of various tungsten oxide photocatalysts synthesized so far is more positive than the hydrogen evolution potential of water reduction, and is only suitable for the oxygen evolution half reaction of photoelectrochemical water decomposition under applied bias (see Y. Liu, et al., Adv. Energy Mater .2016, 6 , 1600437; W. Li, et al., ACS Nano 2014, 8 , 11770–11777; G.Wang, et al., Energy Environ. Sci .2012, 5 , 6180–6187.), or as a plasmon resonance sensitizer for the hydrogen evolution half-reaction of water splitting in the presence of a sacrificial reagent (Y. Lu, et al., Adv. Funct. Mater. 2022, 32 , 2203638.), but cannot achieve complete photolysis of water. However, tungsten oxide catalysts have excellent properties such as low raw material price and synthesis cost, tungsten atoms' inherent ultra-high thermal catalytic activity for hydrogen and oxygen evolution, good structural stability, excellent light corrosion resistance, and ultra-long service life (S. Chen, L.-W. Wang, Chem. Mater .2012, 24 ,3659–3666.), which can undoubtedly better meet the needs of industrial-scale photocatalytic water splitting. In particular, the variable valence of tungsten ions makes it easy to be doped and replaced by many other metal ions with different valence states, thus giving it an adjustable energy band structure that can meet the energy level structure and light absorption characteristics required for complete photocatalytic water splitting. By combining appropriate heteroatom doping with crystal structure design and manufacturing, the composition and surface structure of tungsten oxide photocatalysts (highly active surface and effective photogenerated carrier separation) are regulated to obtain the appropriate electronic structure and ideal surface structure for complete water splitting, thereby significantly improving its activity and realizing the innovation of complete photocatalytic water splitting, thereby improving the preparation efficiency of green hydrogen and reducing costs.
[0005] To this end, it is necessary to explore a suitable doping method to synthesize metal ion-doped tungsten oxide catalysts and regulate the composition, morphology and exposed crystal surface structure, and then establish a low-cost and reliable synthesis process route to facilitate mass production and ensure stable product quality. This is of great significance for promoting the development of zero-carbon hydrogen production by complete photolysis of water and meeting the low-cost, green, sustainable and safe requirements of the hydrogen production industry. Summary of the invention
[0006] 1. Technical problems to be solved:
[0007] Most of the existing complete photocatalysts for water splitting have low efficiency, with the conversion efficiency of solar energy to hydrogen (STH) being less than 1%. The raw materials used for high-activity photocatalysts are scarce and expensive, such as gallium-indium compounds. The photocatalysts obtained have poor light corrosion resistance and short service life. In addition, the synthesis method is cumbersome and complex, which is not conducive to large-scale preparation. In view of the above technical problems, the present invention provides a synthesis method of a chromium ion-doped tungsten oxide complete photocatalyst flat reactor.
[0008] 2. Technical solution:
[0009] A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor comprises the following steps:
[0010] Step 1: Sodium tungstate and chromium acetate are fully dissolved in water and then mixed with glacial acetic acid to obtain a reaction solution. The volume ratio of water to glacial acetic acid is 1:1, wherein the concentrations of sodium tungstate, chromium acetate, citric acid or trisodium citrate are 0.01 ~ 1 mol L −1 , 1 × 10 −3 ~ 0.4 mol L −1 , 0 ~ 2 mol L −1 , and maintaining the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate in the solution at 1: 0.1 ~ 0.4: 0 ~ 2, and then transferring to a stainless steel autoclave reactor with a polytetrafluoroethylene liner;
[0011] Step 2: immerse the surface pretreated nickel foam in the reactant solution, seal the autoclave reactor and heat it to any temperature in the range of 120 ºC to 220 ºC for 5 to 25 hours, cool the reactor to room temperature and release the pressure to obtain the nickel foam covered with chromium-doped tungsten oxide with micro-nano structure, wash it with warm water and dry it for later use;
[0012] Step 3: Place the chromium-doped tungsten oxide nickel foam dried in step 2 in a vacuum environment at 4 ~ 6 ºC / min. −1 The temperature was raised to 300-400°C and annealed at this temperature for 1.5-2.5 hours to obtain a chromium-doped tungsten oxide photocatalyst flat-plate reactor with a strong bond to the nickel foam and improved crystallinity.
[0013] Furthermore, the surface pretreatment of nickel foam was carried out by using isopropanol, 0.1-1 mol L −1 The nickel foam was treated with ultrasonic waves at 25 to 45 °C for 10 to 30 minutes to remove the grease and oxide layer on the surface of the nickel foam.
[0014] Preferably, the volume of the stainless steel autoclave reactor is 1.125 to 2.5 times the volume of the reaction solution.
[0015] Preferably, the nickel foam is in sheet or mesh form, with an area of 1 × 1 to 50 × 50 cm 2 .
[0016] Preferably, the temperature of the warm water washing in step 2 is 40 to 45°C, washing is performed 2 to 4 times, and drying is performed at 60°C.
[0017] The synthesis method of the chromium ion doped tungsten oxide complete photolysis water catalyst flat plate reactor of the present invention can obtain two different series of photocatalyst flat plate reactors according to whether citric acid or trisodium citrate participates in the reaction.
[0018] When citric acid or trisodium citrate is not involved in the reaction, chromium-doped tungsten oxide is obtained as octahedral micron particles, which are recorded as Cr-WO3 / NF-I series photocatalyst flat reactors. The side length of the octahedral micron particles of the Cr-WO3 / NF-I series photocatalyst is 10 ~ 50 μm, and the specific surface area ( S BET ) is 12.3 ~ 15.0 m 2 g ‒1 , the atomic ratio of chromium to tungsten is 1: 5.0 ~ 25.4, and the light absorption starting wavelength (λ onset ) is 565 nm, and the complete photolysis of water solar energy to hydrogen (STH) conversion efficiency is 4.3%~5.1%.
[0019] When citric acid or trisodium citrate is involved in the reaction, chromium-doped tungsten oxide is obtained in the form of octahedral nanoparticles, which are denoted as Cr-WO3 / NF-II series photocatalyst flat reactors. The side length of the Cr-WO3 / NF-II series nano-octahedral photocatalyst is 70-700 nm, and the specific surface area ( S BET ) is 29.7 ~ 34.9 m 2 g ‒1 , the atomic ratio of chromium to tungsten is 1:5.2 ~ 26.6; the light absorption starting wavelength (λ onset ) is 570 nm, and the complete photolysis of water solar energy to hydrogen (STH) conversion efficiency is 4.6%~6.1%.
[0020] 3. Beneficial effects:
[0021] Compared with the prior art, the complete photocatalytic water splitting flat reactor and its synthesis method provided by the present invention have the following advantages: chromium ions are doped into the tungsten trioxide lattice to improve the electronic structure and obtain an energy band structure that perfectly matches the water redox potential; chromium ions are doped above the valence band in the forbidden band of tungsten oxide to introduce a new energy level (i.e., impurity energy level), which significantly reduces the band gap width of tungsten oxide and expands the visible light absorption range. The use of citric acid or sodium citrate reduces the size of the photocatalytic water splitting catalyst particles, increases the catalyst specific surface area (number of active sites) and scattering light ability, enhances the light absorption ability and sufficient contact with water molecules, thereby enhancing the catalytic activity and saving the amount of catalyst used; the highly porous structure of the nickel foam (or nickel mesh) substrate promotes the diffusion and mass transfer of water molecules to the surface of the photocatalyst; the inherent ultra-high hydrogen evolution of chromium oxide itself (Q.Wang, et al., Nat. Mater .2019, 18 , 827–832; Z. Wang, et al., Nat. Catal .2018, 1 ,756–763.) and tungsten oxide oxygen evolution (FMPesci, et al., J. Phys. Chem. Lett .2011, 2 , 1900–1903; X. Liu, et al., Phys. Chem. Chem. Phys .2012, 14 , 7894–7911.) Thermocatalytic activity increases the water decomposition rate; good structural stability and excellent light corrosion resistance; the high earth abundance of chromium and tungsten elements ensures the low raw material price and synthesis cost of chromium-doped tungsten oxide catalyst. The above characteristics significantly improve the activity of the complete photocatalytic water splitting catalyst (solar energy → hydrogen (STH) conversion efficiency value 4.3%~6.1%), service life, and reduce its cost price. The addition of carriers such as nickel foam, nickel sheet, or nickel mesh leads to the direct formation of an integrated complete photocatalytic water splitting catalyst panel after the synthesis reaction is completed. The photocatalyst is evenly distributed to avoid aggregation, ensuring full contact with water and easy separation of the photocatalyst from water; the primary and secondary structure size distribution range of the photocatalyst is narrow, and the shape of the hierarchical nanostructure is uniform and consistent, ensuring the stability and repeatability of the catalytic performance; the size of the nickel foam, nickel sheet, or nickel mesh carrier in this reaction route is adjustable, and the photocatalyst flat reactor can be scaled up and has stable quality. The above advantages lay the foundation for the application of this preparation method in low-cost and large-scale zero-carbon green hydrogen production. Therefore, the preparation method of the chromium-doped tungsten oxide / nickel foam (or nickel sheet, nickel mesh) integrated photocatalyst flat-plate reactor provided by the present invention is suitable for large-scale production and has extremely broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The Cr-WO3 / NF−I(a) photocatalyst flat-plate reactor prepared in Example 1 of the present invention is: (A) low magnification scanning electron microscope (SEM), (B) high magnification scanning electron microscope (SEM) image, (C) X-ray diffraction (XRD) spectrum (the diffraction peaks marked with crystal plane index and asterisks are respectively attributed to cubic structure hydrated tungsten trioxide (mixed phase of WO3∙0.5H2O and W2O6∙H2O) and foam nickel substrate), (D) arbitrarily selected scanning electron microscope image (upper left) and corresponding energy dispersive X-ray (EDX) spectrum element distribution image, (E) quantitative analysis of element content energy dispersive X-ray spectrum (SEM-EDX) map, (F) X-ray photoelectron spectrum full scan spectrum, (G) tungsten 4f high resolution spectrum, (H) chromium 2p high resolution spectrum;
[0023] Figure 2 The Cr-WO3 / NF−I(a) photocatalyst flat-plate reactor prepared in Example 1 of the present invention is as follows: (I) UV-visible near-infrared absorption spectra of Cr-WO3 / NF−I(a) and undoped cubic hydrated tungsten trioxide obtained by UV-visible diffuse reflectance spectroscopy (the absorption in the long-wave range comes from the localized surface plasmon resonance effect of hydrated tungsten trioxide), (J) N2 (77.4 K) adsorption-desorption isotherm, (K) the corresponding BJH pore size distribution curve;
[0024] Figure 3 The Cr-WO3 / NF−II(a) photocatalyst flat-plate reactor prepared in Example 4 of the present invention is: (A) low magnification scanning electron microscope (SEM), (B) high magnification scanning electron microscope (SEM), (C) transmission electron microscope (TEM) image of Cr-WO3 photocatalyst particles, (D) X-ray diffraction (XRD) spectrum (the diffraction peaks marked with crystal plane indices and asterisks are respectively attributed to cubic structure hydrated tungsten trioxide (mixed phase of WO3∙0.5H2O and W2O6∙H2O) and foamed nickel substrate), (E) high resolution transmission electron microscope (HRTEM) image of Cr-WO3 (the plane with a spacing of 2.568 Å in the figure is attributed to the (400) lattice plane of cubic structure chromium-doped hydrated tungsten trioxide), (F) quantitative analysis of element content energy dispersive X-ray spectroscopy (SEM-EDX) map, (G) full scan spectrum of X-ray photoelectron spectroscopy, (H) high resolution spectrum of tungsten 4f;
[0025] Figure 4The Cr-WO3 / NF−II(a) photocatalyst flat-plate reactor prepared in Example 4 of the present invention is as follows: (I) chromium 2p high-resolution spectrum, (J) UV-visible near-infrared absorption spectrum of Cr-WO3 / NF−II(a) and undoped cubic hydrated tungsten trioxide obtained by UV-visible diffuse reflectance spectroscopy (the absorption in the long-wave range comes from the localized surface plasmon resonance effect of hydrated tungsten trioxide); (K) N2 (77.4 K) adsorption-desorption isotherm, and (L) the corresponding BJH pore size distribution curve.
[0026] Figure 5 The Cr-WO3 / NF−II(b) photocatalyst flat-plate reactor prepared in Example 5 of the present invention is as follows: (A) low magnification scanning electron microscopy (SEM), (B) high magnification scanning electron microscopy (SEM), (C) transmission electron microscopy (TEM) of Cr-WO3 photocatalyst particles, (D) arbitrarily selected scanning electron microscopy image (upper left) and the corresponding energy dispersive X-ray (EDX) spectrum element distribution image, (E) quantitative analysis of element content energy dispersive X-ray spectrum (SEM-EDX) diagram, (F) X-ray diffraction (XRD) spectrum (the diffraction peaks marked with crystal plane indices and asterisks are attributed to cubic tungsten trioxide (mixed phase of WO3∙0.5H2O and W2O6∙H2O) and nickel foam substrate, respectively), (G) high resolution transmission electron microscopy (HRTEM) image of Cr-WO3 octahedral nanoparticles (the spacing in the figure is 2.564 Å and 1.813 Å). The planes at 45° to each other belong to the (400) and (440) lattice planes of cubic chromium-doped hydrated tungsten trioxide, respectively. (H) Full scan spectrum of X-ray photoelectron spectroscopy;
[0027] Figure 6 The Cr-WO3 / NF−II(b) photocatalyst flat-plate reactor prepared in Example 5 of the present invention is as follows: (I) tungsten 4f high-resolution spectrum, (J) chromium 2p high-resolution spectrum; (K) UV-visible near-infrared absorption spectrum of Cr-WO3 / NF−II(b) and undoped cubic hydrated tungsten trioxide obtained by UV-visible diffuse reflectance spectroscopy (the absorption in the long-wave range comes from the localized surface plasmon resonance effect of hydrated tungsten trioxide); (L) N2 (77.4 K) adsorption-desorption isotherm; (M) corresponding BJH pore size distribution curve;
[0028] Figure 7 This is a digital photograph of the appearance of the Cr-WO3 / NF−II (b) photocatalyst flat-plate reactor prepared in Example 5 of the present invention. The missing catalyst on the edge of the nickel foam (NF) in the figure is due to the obstruction of the clamp fixing the NF;
[0029] Figure 8The various Cr-WO3 / NF photocatalyst flat-plate reactors (A) prepared in Examples 1, 4 and 5 of the present invention are equipped with a cut-off filter ( λ ≥ 420 nm) under 400 W xenon lamp irradiation, the amount and molar ratio of photocatalytic H2 and O2 released from pure water change with time (data points: circle, Cr-WO3 / NF−I (a); triangle, Cr-WO3 / NF−II (a); diamond, Cr-WO3 / NF−II (b)), (B) under the condition of equipped with cut-off filter ( λ ≥ 420 nm), the Cr-WO3 / NF−II(b) and hydrated WO3 / NF flat reactors catalyze the release of H2 and O2 from pure water under the irradiation of a 400 W xenon lamp; (C) action spectrum of Cr-WO3 / NF−I(a); (D) action spectrum of Cr-WO3 / NF−II(a); (E) action spectrum of Cr-WO3 / NF−II(b); the above action spectra are the comparison between the apparent quantum efficiency (AQE) of hydrogen production from the complete decomposition of pure water as a function of irradiation wavelength and the corresponding UV−visible near-infrared absorption spectra. The 400 W xenon lamp was equipped with various bandpass filters for the apparent quantum efficiency (AQE) test;
[0030] Fig. 9 The photoelectron spectra (PESA) of (A) Cr-WO3 / NF-I (a), (B) Cr-WO3 / NF-II (a), and (C) Cr-WO3 / NF-II (b) photocatalyst flat-plate reactors prepared in Examples 1, 4, and 5 of the present invention measured in air; (D) various Cr-WO3 / NF photocatalyst flat-plate reactors were measured by ( αhv ) 0.5 and photon energy ( hv ) relationship curve to obtain the band gap energy ( E g ) values (curves: dotted line, Cr-WO3 / NF−I(a); dash-dot line, Cr-WO3 / NF−II(a); solid line, Cr-WO3 / NF−II(b)), (E) Band gap energy of various Cr-WO3 / NF photocatalyst flat-plate reactors ( E g ), the energy level positions of the conduction band bottom minimum (CBM) and the valence band top maximum (VBM) (left, Cr-WO3 / NF−I(a); middle, Cr-WO3 / NF−II(a); right, Cr-WO3 / NF−II(b)), and the redox potential position of water decomposition. DETAILED DESCRIPTION
[0031] The present invention will be described in detail below with reference to the accompanying drawings.
[0032] As attached Figure 1To Attachment Fig. 9 As shown,
[0033] Example 1
[0034] A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor comprises the following steps:
[0035] Step 1: Dissolve 0.132 ~ 13.195 g of sodium tungstate dihydrate and 0.0045 ~ 0.4585 g of chromium acetate in 20 ml of water, then add an equal volume of glacial acetic acid and mix thoroughly. The sodium tungstate concentration is 0.01 ~ 1 mol L −1 , chromium acetate concentration: 1 × 10 −3 ~ 0.1 mol L −1 , and the molar ratio of sodium tungstate to chromium acetate is maintained at 1:0.1, and then the reaction mixture is transferred to a 50 ml stainless steel autoclave reactor lined with clean polytetrafluoroethylene;
[0036] Step 2: 4 to 6 tablets were sequentially washed with isopropanol and dilute hydrochloric acid (0.1 mol L −1 ), anhydrous ethanol, and ultrasonically treated at room temperature (15 to 30°C) for 10 to 30 minutes to remove the surface grease and oxide layer of nickel foam (or nickel sheet, nickel mesh) (1 × 1 to 10 × 10 cm 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to 180 ºC for 12 hours, then cooled to room temperature to obtain a foamed nickel (or nickel sheet, nickel mesh) covered with chromium-doped tungsten oxide, which is taken out, washed three times in warm water at 40 to 45 ºC, and then dried at 60 ℃ for use;
[0037] Step 3: Heat the chromium-doped tungsten oxide / nickel foam (or nickel sheet, nickel mesh) obtained in step 2 in a vacuum at 4~6 ºC min −1 The temperature is heated to 300 ~ 400 ºC at a heating rate and annealed at this temperature for 1.5 ~ 2.5 hours to further obtain chromium-doped tungsten oxide (a mixed phase of WO3∙0.5H2O and W2O6∙H2O) micron particles with octahedral shape supported on nickel foam (or nickel sheet, nickel mesh), namely Cr-WO3 / NF−I(a) photocatalyst flat-plate reactor.
[0038] like Figure 1 As shown, the SEM of the Cr-WO3 / NF−I(a) photocatalyst flat-plate reactor prepared in Example 1 above ( Figure 1 A and Figure 1B) It can be seen that when the molar ratio of sodium tungstate to chromium acetate is 1:0.1, the shape of the Cr-WO3 / NF−I(a) catalyst is regular octahedral micron particles, and the side length of the octahedral micron particles is 10 ~ 50 μm. XRD spectrum ( Figure 1 C) It is confirmed that the active components of Cr-WO3 / NF−I(a) are composite oxides of cubic structure WO3∙0.5H2O and W2O6∙H2O. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) spectrum element distribution map ( Figure 1 D) and energy dispersive X-ray spectroscopy (EDX) quantitative analysis ( Figure 1 E) showed that Cr-WO3 / NF−I(a) was composed of W, Cr, and O elements, and the atomic ratio of W / Cr / O was 24.13:0.95:74.42 (Table 1), and proved that W, Cr, and O were evenly distributed in the Cr-WO3 / NF−I(a) photocatalyst ( Figure 1 D). XPS full scan image ( Figure 1 F) and element high resolution spectrum ( Figure 1 G and 1H) show that the active catalyst components of Cr-WO3 / NF−I(a) are composed of W, Cr, and O elements, and the atomic ratio of W / Cr / O is 24.23:0.89:74.88 (Table 1). UV-visible near-infrared absorption spectrum ( Figure 2 I) shows the onset absorption wavelength of the bandgap transition (λ onset ) is about 565 nm, and there is localized surface plasmon resonance absorption at the long wavelength, which is similar to the undoped hydrated tungsten trioxide (λ onset = 520 nm), the initial absorption wavelength of the Cr-WO3 / NF−I(a) photocatalyst is significantly red-shifted, and it is obvious that chromium ion doping causes a significant increase in the visible light absorption range of tungsten oxide. Cr-WO3 / NF−I(a) shows a type IV N2 physical adsorption isotherm ( Figure 1 G), because the gaps and holes between the octahedral micron particles show the characteristics of mesoporous materials with typical H3 loops ( Figure 1 H). Specific surface area ( S BET ) is 12.3 m 2 g ‒1 (Table 1).
[0039] like Figure 8 As shown in A, the Cr-WO3 / NF-I(a) photocatalyst flat-plate reactor prepared in Example 1 is equipped with a cutoff filter ( λ ≥ 420 nm) under 400 W xenon lamp irradiation, the average rates of hydrogen and oxygen evolution were 0.102 mmol h − 1 cm−2 and 0.0506 mmol h −1 cm −2 , the ratio of hydrogen evolution rate to oxygen evolution rate is 2.02 ( Figure 8 A). The conversion efficiency of solar energy to hydrogen (STH) is 4.3% (Table 1). Figure 5 The action spectrum in C shows that the apparent quantum efficiency (AQE) of complete water splitting changes with the irradiation wavelength, which is consistent with the change of UV-visible absorption with wavelength obtained by diffuse reflectance spectroscopy. The generation of hydrogen and oxygen is completely consistent with the starting wavelength of light absorption, indicating that the photolysis of water proceeds through interband transitions. The maximum value (VBM) of the valence band top measured by photoelectron spectroscopy (PESA) is 5.740 eV ( Fig. 9 A), the band gap energy of Cr-WO3 / NF-I(a) photocatalyst was calculated by UV-visible near-infrared absorption spectroscopy ( E g ) is 2.185 eV ( Fig. 9 D), according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the conduction band bottom minimum (CBM) is calculated to be 3.555 eV, that is, the potentials of the valence band top maximum (VBM) and the conduction band bottom minimum (CBM) relative to the standard hydrogen electrode are 1.28 V and −0.90 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition.
[0040] Example 2
[0041] Only step 1 of Example 1 is replaced as follows: 0.132 to 13.195 g of sodium tungstate dihydrate and 0.009 to 0.917 g of chromium acetate are fully dissolved in 20 ml of water, and then an equal volume of glacial acetic acid is added and mixed thoroughly, and the sodium tungstate concentration is: 0.01 to 1 mol L −1 , chromium acetate concentration: 2 × 10 −3 ~ 0.2 mol L −1 , and the molar ratio of sodium tungstate to chromium acetate is maintained at 1:0.2, and then the above reaction mixture is transferred to a 50 ml stainless steel autoclave reactor lined with clean polytetrafluoroethylene; the other steps are the same as in Example 1 to obtain a Cr-WO3 / NF−I(b) photocatalyst flat reactor. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) spectrum element distribution map and energy dispersive X-ray spectrum (EDX) quantitative analysis show that Cr-WO3 / NF−I(b) is composed of W, Cr and O elements, and the atomic number ratio of W / Cr / O is 21.65: 3.48: 74.87 (Table 1). Specific surface area ( S BET ) is 15.0 m 2g ‒1 , the UV-visible near-infrared absorption spectrum shows the onset absorption wavelength of the band gap transition (λ onset ) is around 565 nm, and the complete photolysis of water solar energy to hydrogen (STH) conversion efficiency is 4.8% (Table 1).
[0042] Example 3
[0043] Only step 1 of Example 1 is replaced as follows: 0.132-13.195 g of sodium tungstate dihydrate and 0.018-1.834 g of chromium acetate are fully dissolved in 20 ml of water, and then an equal volume of glacial acetic acid is added and mixed thoroughly. The sodium tungstate concentration is 0.01-1 mol L −1 , chromium acetate concentration: 4 × 10 −3 ~ 0.4mol L −1 , and the molar ratio of sodium tungstate to chromium acetate was kept at 1:0.4, and then the reaction mixture was transferred to a 50 ml stainless steel autoclave reactor lined with clean polytetrafluoroethylene; the other steps were the same as in Example 1 to obtain a Cr-WO3 / NF−I(c) photocatalyst flat-plate reactor. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) spectrum element distribution map and energy dispersive X-ray spectrum (EDX) quantitative analysis showed that Cr-WO3 / NF−I(b) was composed of W, Cr and O elements, and the atomic number ratio of W / Cr / O was 20.94: 4.13: 74.93 (Table 1). Specific surface area ( S BET ) is 13.7 m 2 g ‒1 , the UV-visible near-infrared absorption spectrum shows the onset absorption wavelength of the band gap transition (λ onset ) is around 565 nm, and the complete photolysis of water solar energy to hydrogen (STH) conversion efficiency is 5.1% (Table 1).
[0044] Example 4
[0045] A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor comprises the following steps:
[0046] Step 1: 0.132 ~ 13.195 g sodium tungstate dihydrate, 0.0045 ~ 0.4585 g chromium acetate, 0.077 ~ 7.685 g citric acid or 0.118 ~ 11.764 g trisodium citrate dihydrate are fully dissolved in 20 ml water, then an equal volume of glacial acetic acid is added and mixed thoroughly. The sodium tungstate concentration is 0.01 ~ 1 mol L −1 , chromium acetate concentration: 1 × 10 −3 ~0.1 mol L −1, citric acid or trisodium citrate concentration: 0.01 ~ 1 mol L −1 , and the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate is maintained at 1:0.1:1, and then the reaction mixture is transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene;
[0047] Step 2: 4 to 6 tablets were sequentially washed with isopropanol and dilute hydrochloric acid (0.1 mol L −1 ), anhydrous ethanol, and ultrasonically treated at room temperature (15 to 30°C) for 10 to 30 minutes to remove the surface grease and oxide layer of nickel foam (or nickel sheet, nickel mesh) (1 × 1 to 10 × 10 cm 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to 180 ºC, reacted for 12 hours, and then cooled to room temperature to obtain a foamed nickel (or nickel sheet, nickel mesh) covered with chromium-doped tungsten oxide. It is taken out, washed three times in warm water at 40 ~ 45 ºC, and dried at 60 ℃ for use.
[0048] Step 3: Heat the chromium-doped tungsten oxide / nickel foam (or nickel sheet, nickel mesh) obtained in step 2 in a vacuum at 4~6 ºC min −1 The temperature is heated to 300 ~ 400 ºC at a heating rate and annealed at this temperature for 1.5 ~ 2.5 hours to further obtain chromium-doped tungsten oxide (a mixed phase of WO3∙0.5H2O and W2O6∙H2O) nanoparticles with octahedral shape supported on nickel foam (or nickel sheet, nickel mesh), namely Cr-WO3 / NF−II(a) photocatalyst flat-plate reactor.
[0049] like Figure 3-4 As shown, the SEM of the Cr-WO3 / NF−II(a) photocatalyst flat-plate reactor prepared in Example 4 above ( Figure 3 A. Figure 3 B) and TEM images ( Figure 3 C) It can be seen that when the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate is 1:0.1:1, the shape of the Cr-WO3 / NF−II(a) catalyst is octahedral nanoparticles, and the side length of the octahedral nanoparticles is 70 ~ 700 nm. XRD spectrum ( Figure 3 D) It is confirmed that the Cr-WO3 / NF−II(a) photocatalyst is a cubic hydrated tungsten trioxide (composite oxide of WO3∙0.5H2O and W2O6∙H2O). High-resolution transmission electron microscopy (HRTEM) images also confirm that the Cr-WO3 / NF−II(a) catalyst is a cubic hydrated tungsten trioxide ( Figure 3 E). Energy dispersive X-ray spectroscopy (EDX) quantitative analysis ( Figure 3 F) shows that Cr-WO3 / NF−II(a) is composed of W, Cr and O elements, and the atomic ratio of W / Cr / O is 24.21:0.91:74.88 (Table 1). XPS full scan image ( Figure 3 G) and element high resolution spectrum ( Figure 3 H and 4I) show that the active components of Cr-WO3 / NF−II(a) are composed of W, Cr, and O elements, and the atomic ratio of W / Cr / O is 24.16:1.01:74.83. UV−visible near-infrared absorption spectrum ( Figure 4 J) shows the onset absorption wavelength of the bandgap transition (λ onset ) is about 570 nm, and there is localized surface plasmon resonance absorption at the long wavelength, which is similar to the undoped hydrated tungsten trioxide (λ onset = 520 nm), the onset absorption wavelength of the Cr-WO3 / NF−II(a) photocatalyst is significantly red-shifted, indicating that chromium ion doping causes a significant expansion of the visible light absorption range of tungsten oxide. Cr-WO3 / NF−II(a) shows a type IV N2 physical adsorption isotherm ( Figure 4 K), because the gaps and holes between the octahedral nanoparticles show the characteristics of mesoporous materials with typical H3 loops ( Figure 4 L). Specific surface area ( S BET ) is 29.7m 2 g ‒1 (Table 1).
[0050] like Figure 8 As shown in A, the Cr-WO3 / NF-II(a) photocatalyst flat-plate reactor prepared in Example 4 is equipped with a cutoff filter ( λ ≥ 420 nm) under 400 W xenon lamp irradiation, the average rates of hydrogen and oxygen evolution were 0.119 mmol h − 1 cm −2 and 0.0604 mmol h −1 cm −2 , the ratio of hydrogen evolution rate to oxygen evolution rate is 1.97, which is very close to 2 ( Figure 8 A). The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 4.6% (Table 1). The change of the apparent quantum efficiency (AQE) of complete water splitting with irradiation wavelength is consistent with the change of UV-visible absorption with wavelength. The production of hydrogen and oxygen is completely consistent with the starting wavelength of light absorption, indicating that the photolysis of water is carried out through interband transition ( Figure 8 D). The valence band maximum (VBM) measured by photoelectron spectroscopy (PESA) is 5.76 eV ( Fig. 9B), the band gap energy of Cr-WO3 / NF-II(a) photocatalyst was calculated by UV-visible near-infrared absorption spectra ( E g ) is 2.190 eV ( Fig. 9 D), according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.570 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 1.29 V and −0.89 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition.
[0051] Example 5
[0052] A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor comprises the following steps:
[0053] Step 1: 0.132 ~ 13.195 g sodium tungstate dihydrate, 0.009 ~ 0.917 g chromium acetate, 0.077 ~ 7.685 g citric acid or 0.118 ~ 11.764 g trisodium citrate dihydrate are fully dissolved in 20 ml water, then an equal volume of glacial acetic acid is added and mixed thoroughly. The sodium tungstate concentration is 0.01 ~ 1 mol L −1 , chromium acetate concentration: 2 × 10 −3 ~ 0.2 molL −1 , citric acid or trisodium citrate concentration: 0.01 ~ 1 mol L −1 , and the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate is maintained at 1:0.2:1, and then the reaction mixture is transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene;
[0054] Step 2: 4 to 6 tablets were sequentially washed with isopropanol and dilute hydrochloric acid (0.1 mol L −1 ), anhydrous ethanol, and ultrasonically treated at room temperature (15 to 30°C) for 10 to 30 minutes to remove the surface grease and oxide layer of nickel foam (or nickel sheet, nickel mesh) (1 × 1 to 10 × 10 cm 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to 180 ºC, reacted for 12 hours, and then cooled to room temperature. The nickel foam (or nickel sheet, nickel mesh) covered with chromium-doped tungsten oxide is taken out, washed three times in warm water at 40 ~ 45 ºC, and dried at 60 ℃ for use;
[0055] Step 3: Heat the chromium-doped tungsten oxide / nickel foam (or nickel sheet, nickel mesh) obtained in step 2 in a vacuum at 4~6 ºC min−1 The temperature is heated to 300 ~ 400 ºC at a heating rate and annealed at this temperature for 1.5 ~ 2.5 hours to further obtain chromium-doped tungsten oxide (a mixed phase of WO3∙0.5H2O and W2O6∙H2O) nanoparticles with octahedral shape supported on nickel foam (or nickel sheet, nickel mesh), namely Cr-WO3 / NF−II(b) photocatalyst flat-plate reactor.
[0056] like Figure 5-6 As shown, the SEM of the Cr-WO3 / NF−II (b) photocatalyst flat-plate reactor prepared in Example 5 above ( Figure 5 A and 5B) and TEM images ( Figure 5 C) It can be seen that when the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate is 1:0.2:1, the shape of the Cr-WO3 / NF−II(b) catalyst is octahedral nanoparticles, and the side length of the octahedral nanoparticles is 70~700 nm. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) spectrum element distribution map ( Figure 5 D) and energy dispersive X-ray spectroscopy (EDX) quantitative analysis ( Figure 5 E) showed that Cr-WO3 / NF−II(b) was composed of W, Cr and O elements, and the atomic ratio of W / Cr / O was 21.48:3.55:74.97 (Table 1), and proved that W, Cr and O were evenly distributed in Cr-WO3 / NF−II(b) photocatalyst ( Figure 5 D). XRD spectrum ( Figure 5 F) Confirms that the Cr-WO3 / NF−II(b) photocatalyst is a cubic structure hydrated tungsten trioxide (composite oxide of WO3∙0.5H2O and W2O6∙H2O). High-resolution transmission electron microscopy (HRTEM) image ( Figure 5 G) and XRD patterns ( Figure 5 F) It is consistently confirmed that the active component of Cr-WO3 / NF−II(b) contains hydrated tungsten trioxide with a cubic structure. Figure 4 Digital photo of a typical sample of Cr-WO3 / NF−II (b) photocatalyst flat-plate reactor with a diameter of 20 cm. XPS full scan ( Figure 5 H) and elemental high resolution spectra ( Figure 6 I and 6J) show that Cr-WO3 / NF−II(b) is composed of W, Cr, and O elements, and the atomic ratio of W / Cr / O is 21.66:3.37:74.97. UV−visible near-infrared absorption spectrum ( Figure 6 K) shows the onset absorption wavelength of the band gap transition (λ onset) is about 570 nm, and there is localized surface plasmon resonance absorption at the long wavelength, which is similar to the undoped hydrated tungsten trioxide (λ onset = 520 nm), the onset absorption wavelength of the Cr-WO3 / NF−II(b) photocatalyst is significantly red-shifted, indicating that chromium ion doping causes a significant expansion of the visible light absorption range of tungsten oxide. Cr-WO3 / NF−II(b) shows a type IV N2 physical adsorption isotherm ( Figure 6 L), because the gaps and holes between the octahedral nanoparticles show the characteristics of mesoporous materials with typical H3 loops ( Figure 6 M). Specific surface area ( S BET ) is 34.9 m 2 g ‒1 (Table 1).
[0057] like Figure 8 As shown in A, the Cr-WO3 / NF-II (b) photocatalyst flat-plate reactor prepared in Example 5 is equipped with a cutoff filter ( λ ≥ 420 nm) under 400 W xenon lamp irradiation, the average rates of hydrogen and oxygen evolution were 0.145 mmol h − 1 cm −2 and 0.0727 mmol h −1 cm −2 , the ratio of hydrogen evolution rate to oxygen evolution rate is 1.99 ( Figure 8 A). The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 5.7% (Table 1). The action spectrum shows that the change of the apparent quantum efficiency (AQE) of complete water splitting with the irradiation wavelength is consistent with the change of UV-visible absorption with wavelength. The production of hydrogen and oxygen is completely consistent with the starting wavelength of light absorption, indicating that the photolysis of water is carried out through interband transition ( Figure 8 E). Figure 8 B shows the Cr-WO3 / NF−II(b) photocatalyst flat-plate reactor immersed in water (see Figure 8 (B, right) Under the irradiation of a 400 W xenon lamp, a large number of bubbles are precipitated in the water and the degree of bubbles produced by its catalysis is much higher than that of pure hydrated WO3 without Cr doping synthesized under the same conditions (see Figure 8 The valence band maximum (VBM) measured by photoelectron spectroscopy (PESA) is 5.73 eV ( Fig. 9 C), Cr-WO was calculated by UV-visible near-infrared absorption spectroscopy. 3 / Band gap energy of NF−II(b) photocatalyst ( E g ) is 2.190 eV ( Fig. 9D), according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.540 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 1.28 V and −0.91 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition.
[0058] Example 6
[0059] Only step 1 of Example 5 is replaced as follows: 0.132 to 13.195 g of sodium tungstate dihydrate, 0.018 to 1.834 g of chromium acetate, 0.154 to 15.37 g of citric acid or 0.236 to 25.328 g of trisodium citrate dihydrate are fully dissolved in 20 ml of water, and then an equal volume of glacial acetic acid is added and mixed thoroughly. The sodium tungstate concentration is 0.01 to 1 mol L −1 , chromium acetate concentration: 4 × 10 −3 ~ 0.4 mol L −1 , citric acid or trisodium citrate concentration: 0.02~2 mol L −1 , and the molar ratio between sodium tungstate, chromium acetate, citric acid or trisodium citrate is maintained at 1:0.4:2. The above reaction mixture is then transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene, and the other steps are the same as in Example 5. A Cr-WO3 / NF−II(c) photocatalyst flat-plate reactor is obtained. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) spectrum element distribution map and energy dispersive X-ray spectrum (EDX) quantitative analysis show that Cr-WO3 / NF−I(b) is composed of W, Cr and O elements, and the atomic number ratio of W / Cr / O is 21.06: 4.05: 74.89 (Table 1). Specific surface area ( S BET ) is 31.5m 2 g ‒1 , the UV-visible near-infrared absorption spectrum shows the onset absorption wavelength of the band gap transition (λ onset ) is around 570 nm, and the conversion efficiency of complete photolysis of water solar energy to hydrogen (STH) is 6.1% (Table 1).
[0060] The raw material molar ratio, product composition and performance data of the Cr-WO3 / NF photocatalyst flat-plate reactor prepared in Examples 1-6 are summarized as shown in Table 1:
[0061]
[0062] In summary, the UV-visible-near infrared absorption spectra of various Cr-WO3 / NF photocatalyst flat-plate reactors indicate that there is a significant concentration of band gap vacancy levels due to chromium doping ( E V ). This indicates that there are more defect levels in the band gap, which narrows the energy band width and makes the visible light absorption range wider; in addition, the chemical catalytic effect of chromium oxide can significantly accelerate the surface reduction half-reaction; in addition, the adsorption energy of water molecules on the surface of Cr-WO3 photocatalyst is adjusted, so that it has a lower reaction energy barrier. Cr-WO3 / NF photocatalyst has a conduction band bottom that is negative to the potential of water decomposition hydrogen reaction, and a very wide visible light absorption range. In particular, the Cr-WO3 / NF−II series controlled by citric acid or sodium citrate has a large specific surface area, which accelerates the hydrogen evolution reaction and shows the highest complete water decomposition activity. Nanoparticles have a solid structure, which ensures that the catalyst has an excellent activity life.
[0063] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.
Claims
1. A method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat reactor, characterized in that: The following steps are involved: Step 1: Sodium tungstate and chromium acetate are fully dissolved in water and then mixed with glacial acetic acid to obtain a reaction solution. The volume ratio of water to glacial acetic acid is 1:1, wherein the concentrations of sodium tungstate, chromium acetate, citric acid or trisodium citrate are 0.01 ~ 1 mol L −1 , 1 × 10 −3 ~ 0.4 mol L −1 , 0 ~ 2 mol L −1 , and maintaining the molar ratio of sodium tungstate, chromium acetate, citric acid or trisodium citrate in the solution at 1: 0.1 ~ 0.4: 0 ~ 2, and then transferring to a stainless steel autoclave reactor with a polytetrafluoroethylene liner; Step 2: immerse the surface pretreated nickel foam in the reactant solution, seal the autoclave reactor and heat it to any temperature in the range of 120 ºC to 220 ºC for 5 to 25 hours, cool the reactor to room temperature and release the pressure to obtain the nickel foam covered with chromium-doped tungsten oxide with micro-nano structure, wash it with warm water and dry it for later use; Step 3: Place the chromium-doped tungsten oxide nickel foam dried in step 2 in a vacuum environment at 4 ~ 6 ºC min −1 The temperature was raised to 300-400°C and annealed at this temperature for 1.5-2.5 hours to obtain a chromium-doped tungsten oxide photocatalyst flat-plate reactor with a strong bond to the nickel foam and improved crystallinity.
2. The method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor according to claim 1, characterized in that: The surface pretreatment of nickel foam was carried out by using isopropanol and 0.1-1 mol L −1 The nickel foam was treated with ultrasonic waves at 25 to 45 °C for 10 to 30 minutes to remove the grease and oxide layer on the surface of the nickel foam.
3. The method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat reactor according to claim 2, characterized in that: The volume of the stainless steel autoclave reactor is 1.125 to 2.5 times the volume of the reaction solution.
4. The method for synthesizing a chromium ion-doped tungsten oxide complete photolysis water catalyst flat-plate reactor according to any one of claims 1 to 3, characterized in that: Nickel foam is in sheet or mesh form, with an area of 1 × 1 ~ 50 × 50 cm 2 .
5. The method for synthesizing a chromium ion-doped tungsten oxide complete photocatalyst flat reactor according to claim 4, characterized in that: In step 2, the temperature of warm water washing is 40 ~ 45 ºC, wash 2 ~ 4 times, and dry at 60 ℃.
Citation Information
Patent Citations
Synthesis method of tungsten trioxide
CN103011293A
High specific surface area metal doped oxide hollow nanosphere and preparation method thereof
CN104190397A